﻿Perancangan Sistem Pengontrol Keamanan Rumah dengan Smart CCTV Menggunakan Arduino Berbasis Telegram - Dedi Setiawan; Joni Eka Candra; Cosmas Eko Suharyanto (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2019)
The development of increasingly modern times like now, has make us to always be inspired and provide new ideas in developing appropriate and advanced technology, then it needs a tool that can help humans to facilitate access to obtain information, one of them is home security information, because not a few criminal acts that occur in our homes when we are outside, then more supervision is needed, so with that problem created the idea to make a tool (smart cctv) as our home monitor by utilizing the telegram application as a remote controller, serial camera VC0706 as a media image capture, and using the NodeMCU ESP8266 as the controller. After the prototype test results which is conducted each function of each component used already functions in the order specified, when the device is activated NodeMCU ESP8266 will be directly connected to the specified Wi-Fi network, a camera connected to a surveillance monitor can also automatically take pictures at the same time and send images to the Telegram application when the sensor detects movement, the buzzer will also automatically ring so that it can provide information to those around that at our house there is a crime attempt.